A novel large filamentous deltaproteobacterium on hydrothermally inactive sulfide chimneys of the Southern Mariana Trough. (April 2016) - Kato, Shingo; Yamagishi, Akihiko
Abstract: Unusual large filamentous bacteria (LFB) have been found on the deep seafloor environments. They play a significant role in geochemical cycling in the dark environments. However, our knowledge of the spatial distribution and phylogenetic diversity of the LFB on the deep seafloor are still limited due to the inaccessibility to these environments. Here, we report the discovery of a novel LFB on a hydrothermally inactive sulfide chimney in a deep-sea hydrothermal field of the Southern Mariana Trough. Light and electron microscopic observation showed that the width and total length of the LFB were >8 µm and >100 µm, respectively, of which morphology was similar to that of other known LFB such as "cable bacteria" of the Desulfobulbaceae . Analyses of a 16S rRNA gene clone library and fluorescence in situ hybridization revealed that this LFB belongs to the Desulfobulbaceae . The 16S rRNA gene of the LFB showed 94% similarity to those of the reported cable bacteria and cultured deltaproteobacterial species, suggesting that the LFB is a novel cable bacterium of the Desulfobulbaceae . The novel LFB potentially play a role in sulfur cycling on sulfide chimneys at the hydrothermally ceasing or even ceased deep-sea hydrothermal fields. Highlights: We report a novel large filamentous bacterium in a deep-sea sulfide chimney. The bacterium resembles "cable bacteria" phylogenetically and morphologically. Cable bacteria may play a role in sulfur cycling on deep-sea vent fields.